Harmonizing maqasid al-shari’ah with sustainable waste management practices: a conceptual framework for principles and implementation - Shompa, Zohora Azmin; Akbar, Mohamed Aslam; Mohd Mohadis, Hazwani (Emerald Insights, 2025)
Purpose– This paper aims to investigate the principles guiding sustainable waste management practices within the framework of Maqasid al-Shari’ah. The purpose is to address the environmental challenges arising from economic expansion, population growth and resource consumption, which often lead to unsustainable waste management practices and hinder economic growth. The focus is on aligning waste management principles with the ethical objectives outlined in Shari’ah. Design/methodology/approach– Adopting a qualitative content analysis method and an inductive approach to outline the constituent elements that formulate the framework, this study investigates the objectives of Maqasid al-Shari’ah to identify underlying elements crucial for sustainable waste management. Findings– The study reveals how the principles embedded in Maqasid al-Shari’ah provide a foundation for effective waste management practices. The findings emphasize the importance of integrating these principles into humanbehavior to ensure that waste management aligns with the Shari’ah viewpoint. The insights shed light on the role of Maqasid al-Shari’ah in managing waste sustainably and contributing to environmental conservation efforts. Originality/value– This research contributes to the field by offering a unique perspective on waste managementpractices through the lens of Maqasid al-Shari’ah. The study’s originality lies in its exploration of how Islamic ethical objectives can guide sustainable waste management, providing a framework that goes beyond conventional approaches. The incorporation of a comprehensive literature review enhances the authenticity and novelty of the proposed waste managementframework. Keywords Maqasid al-Shari’ah, Waste management practices, Sustainability